ILCYM - Insect Life Cycle Modeling. A software package for developing temperature-based insect phenology models with applications for local, regional and global analysis of insect population and mapping - Sporleder, M.; Carhuapoma, Pablo; Juarez, H.; Gamarra, H.; Simon, R.; Kroschel, Jürgen (International Potato Center, 2017)
This book describes the application of ILCYM software, which supports the development of process-oriented temperature-driven and age-stage structured insect phenology/population models. ILCYM interactively leads the user through the steps for developing insect phenology models, for conducting simulations, and for producing potential population distribution and risk mapping under current or future temperature (climate change) scenarios. The objective of the present document is to explain how the developed modeling approach works; what type of data need to be generated to develop an insect phenology model, what type of data need to be generated to validate a, how are implemented, and what type of insect population analysis will be provided. With the current version of ILCYM the authors intend to share the knowledge gained in insect pest population modeling research at the Agroecology/IPM unit at CIP and provide an open-source computer aided tool, especially for researcher in developing countries, that facilitates the development of own using advanced modeling techniques without being experts in the field.